2020
DOI: 10.1371/journal.pone.0235914
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and facilitators to bidirectional screening of TB-DM in Ghana: Healthcare workers’ perspectives

Abstract: Background The tuberculosis (TB) and diabetes mellitus (DM) co-epidemic continues to increase globally. Low-and middle-income countries bear the highest burden of co-epidemic, and Ghana is no exception. In 2011, the World Health Organisation (WHO) responded to this global challenge by launching a collaborative framework with a view to guide countries in implementing their DM and TB care, prevention and control plans. Subsequently, several countries, including Ghana, adopted this framework and began implementin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 25 publications
2
19
0
2
Order By: Relevance
“…Furthermore, the study reported that stigma due to TB disease, weak collaborative working culture among TB and DM clinics and financial challenges were among the barriers identified to be affecting implementation of effective integration of healthcare services. 48 On the other hand, a cross-sectional study that was conducted in Uganda 43 found that TB screening for DM in routine care was feasible, however, political will and programming issues were to be improved.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the study reported that stigma due to TB disease, weak collaborative working culture among TB and DM clinics and financial challenges were among the barriers identified to be affecting implementation of effective integration of healthcare services. 48 On the other hand, a cross-sectional study that was conducted in Uganda 43 found that TB screening for DM in routine care was feasible, however, political will and programming issues were to be improved.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, varying situations and conditions at each setting should be considered before implementing an integrated approach. For instance, an exploratory study that was conducted in Ghana48 found that staff development and establishment of bidirectional screening services can contribute to facilitating the implementation of integrated care for TB and DM. Furthermore, the study reported that stigma due to TB disease, weak collaborative working culture among TB and DM clinics and financial challenges were among the barriers identified to be affecting implementation of effective integration of healthcare services 48.…”
Section: Discussionmentioning
confidence: 99%
“…There is need to institutionalize bi-directional screening of patients with TB and DM and screen individuals for other co-morbidities such as hypertension which would impact the outcomes. WHO's TB-DM collaborative framework and India's TB strategy recommends screening of TB and DM patients ( 25 ). The framework also encourages implementation research to contextualize to local health systems.…”
Section: Discussionmentioning
confidence: 99%
“…Coordination between TB and NCD control programs needs to be improved to strengthen TB-DM co-management. Though the WHO has also called for the establishment of a formal collaboration between the NCD prevention and TB control programs in TB-DM comanagement [12], TB and DM service integration has been especially challenging as in the past they have been individual vertical programs delivered under different divisions of the health department with little collaboration [41][42][43][44]. In Indonesia, only NTP issued guidelines on TB-DM co-management while the NCD department has not.…”
Section: Suggestions To Further Improve Tb-dm Co-management In Indone...mentioning
confidence: 99%